TINGKAT PENGARUH PROFESIONALISME DAN PENGEMBANGAN KARIR SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI BKPSDMD KABUPATEN WAJO - Salmia Jumri; Rosmayani Rosmayani; Rr Retno Wulansari Kus; Reka Ruslan; Andi Mappellawa (Universitas Ichsan Sidenreng Rappang, 2026)
This study was designed to examine how professionalism and career development can influence employee performance at the Wajo Regency Human Resources Development Agency (BKPSDMD). Employee performance in the public sector depends not only on target achievement but also on individual capacity, including competence, efficiency, effectiveness, and responsibility. Career development is a crucial component that can increase employee productivity through clear career paths, training opportunities, and improved work quality. Quantitative associative analysis and descriptive data analysis were used for data analysis. This study utilized primary data in the form of respondent responses with a total sample of 81 individuals. The data were processed using IBM SPSS 26. The results indicate that (1) Human Resource Development at the Wajo Regency BKPSDMD Office is in the very good category, (2) Employee Performance at the Wajo Regency BKPSDMD is in the very good category, and (3) there is a positive influence between Human Resource Development and Employee Performance at the Wajo Regency BKPSDMD. Data analysis used multiple linear regression to determine the level of influence of Employee Professionalism and HR Career Development on employee performance.